An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Delport, Petrus Albertus (University of Pretoria, 2024)
Thesis (LLD (Law))--University of Pretoria, 2023.